The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1039/c1dt10680e
|View full text |Cite
|
Sign up to set email alerts
|

The first solid phase synthesis of pincer palladium complexes

Abstract: Both dimeric μ-chlorine bridged and monomeric bidentate Pd(II) complexes with SCN hybrid pincer-type ligands, bearing thiophosphoryl group and imine moiety of the benzothiazole ring as coordination arms, formed in the reaction with (PhCN)(2)PdCl(2) under kinetic control (20 °C, dichloromethane solution) were readily converted into the corresponding SCN pincer complexes via solid phase synthesis (neat, 200 °C, 15 min). The synthesis of pincer complexes can be performed also by heating (200 °C, 5 min) of a homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Contrary to what is seen in the NMR spectrum of Complex 3, a molecular ion peak of a 2:2 metal-ligand ratio could not be observed in the mass spectrum of this complex. This strengthens our idea that it can be in transformation in both forms in the solution environment [ 64 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Contrary to what is seen in the NMR spectrum of Complex 3, a molecular ion peak of a 2:2 metal-ligand ratio could not be observed in the mass spectrum of this complex. This strengthens our idea that it can be in transformation in both forms in the solution environment [ 64 ].…”
Section: Discussionsupporting
confidence: 83%
“…Kozlov et al stated in a study they conducted in 2011 that there is a similar situation. In the study, they explained that the pincer Pd(II) complex actively transforms into each other as 1:1 and 2:2 in the structure [ 64 ]. It is thought that this is also the case in Complex 3 and that the formation energies of complexes with metal-ligand ratios of 1:1 and 2:2 are very close to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, palladium complexes 116-119 can be also prepared via thermally induced C-H bond activation in the nonmetallated precursors or homogeneous mixtures of the corresponding ligand and PdCl 2 (PhCN) 2 obtained by grinding of the reagents in a mortar [98]. These reactions appeared to be the first examples of solid-phase synthesis of pincer complexes.…”
Section: Hybrid Pincer Compounds With Thione Sulfur Donorsmentioning
confidence: 97%
“…4 Recently, we have shown that solid-phase cyclopalladation of coordination predecessors can also be performed in multidentate, pincer-type systems with thiophosphoryl and benzothiazole pendant arms. 5 To our surprise, it was found that mixtures of a ligand and PdCl 2 (NCPh) 2 obtained simply by manual grinding in a mortar can also be used as starting materials, efficiently undergoing thermally induced cyclometalation. 5 However, the reactions required high temperatures (200 °C) and were accompanied by sample degradation, resulting in reduced yields of the desired pincer products.…”
Section: Introductionmentioning
confidence: 99%
“…5 To our surprise, it was found that mixtures of a ligand and PdCl 2 (NCPh) 2 obtained simply by manual grinding in a mortar can also be used as starting materials, efficiently undergoing thermally induced cyclometalation. 5 However, the reactions required high temperatures (200 °C) and were accompanied by sample degradation, resulting in reduced yields of the desired pincer products. Therefore, it seemed interesting to investigate whether such a solid-phase strategy is restricted to the particular ligand systems or can become a simple, cheap, efficient, and green alternative to the conventional synthesis of pincer complexes in solution.…”
Section: Introductionmentioning
confidence: 99%